Modelling and analysis of coalbed methane drainage quality in penetrating-strata boreholes considering air leakage - Lizhen Zhao; Tianxuan Hao; Dengke Wang; Jianping Wei; Yang Du; Baisheng Nie; Jie Chen; Zhen Li; Yiju Tang; Fukai Zhang; Bowen Dong; Yuling Xia (Geomatics, Natural Hazards & Risk)
The quality and efficiency of coalbed methane (CBM) drainage are critical for the safe production of coal mining enterprises in China. Air leakage should be prevented during CBM drainage because it can reduce drainage concentration and induce produce accidents such as coal seam spontaneous combustion. However, existing theoretical models for CBM drainage do not consider the air leakage effect. This study sets up a gas–solid coupling theoretical model in which the air leakage effect is taken into account as well as gas diffusion and gas seepage. The influencing factors on the drainage quality of CBM were analyzed using numerical simulation. The results show that the CBM drainage quality linearly improves with the increase of drainage negative pressure, while increasing initial CBM pressure can linearly enhance drainage quality at the early drainage stage. The CBM drainage quality exponentially increases with Langmuir content and exponentially decreases with Langmuir pressure. With the increase of coal’s initial permeability, CBM drainage quality exponentially increases at the early drainage stage but exponentially decreases at the middle and late drainage stages. The new theoretical model effectively depicts the drop in CBM drainage quality and the increase of air leakage during the entire drainage process.